The Living Dead: An Interpretation of the Metaphor of Death in Daoist Inner Alchemy - Qiongke Geng (Religions, 2024)
This article explores the metaphor of death in Qing 清 Dynasty Daoist inner alchemy (neidan 內丹) scriptures, which require practitioners to consider themselves dead or living dead, and argues that this metaphor of death can be traced back to the connotation of the “living dead” proposed by the founder of Complete Perfection (Quanzhen 全真), Wang Chongyang 王重陽, in the Jin 金 Dynasty, who demonstrated his desire for the return of Dao by digging a grave for himself and referring to himself as a living dead man. In addition, this paper also analyzes the psychological connotations represented by the living dead, pointing out that it contains a profound theme of death and rebirth.